(untitled) (International Educators Conference, 2025)
Currently, there are no absolutely reliable methods for preoperative differential diagnosis of benign and malignant thyroid tumors [1]. However, the extent of surgical intervention and the degree of its trauma depend on the correct diagnosis. If cancer is suspected, the minimum extent of intervention includes extrafascial thyroidectomy [2]. This operation can be complicated by paralysis of the recurrent laryngeal nerve and persistent hypoparathyroidism, which requires additional long-term treatment [3, 4]. All patients after thyroidectomy require hormone replacement therapy under the control of laboratory parameters and often - correction of hypocalcemia. Thus, treatment in the postoperative period is labor-intensive and requires high economic costs. At the same time, the recommended extent of intervention in the diagnosis of solid thyroid adenomas is limited to hemithyroidectomy.